EFFECT OF ASHTANGA YOGA PRACTICE ON PSYCHO-PHYSICAL FITNESS ON MEN - Naseev Kumar; Kapruwan, Vijendra Prakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of the study was to find out the effect of Ashtanga Yoga practice on psycho-physical fitness variables on men. For the purpose of the study 20 men from Vishwanand Yoga Kendra, Pune, Maharashtra were randomly selected as subjects for the study, The Single Group Experimental research design was framed for this study. The selected sample underwent one month of AshtangaYoga practice five days in a week for one-hour duration. Pre test and post-test were conducted on the selected psycho-physical fitness variables of men such as Anxiety, Depression, Stress, Flexibility, Body Mass Index. The mean, standard deviation and ‘t’ test were calculated, and the level of significance was set at 0.05. The results showed the significant mean difference in Anxiety level, Depression level, Stress level, Flexibility, and Fat level, of the subjects after 8 weeks of Ashtanga Yoga practice. In conclusion, it appeared that the Ashtanga Yoga practice program resulted in improvement of psycho-physical fitness in men.